2022
DOI: 10.14254/1800-5845/2022.18-4.4
|View full text |Cite
|
Sign up to set email alerts
|

Production Functions for Assessing the Volumes of Agricultural Production in the Regions of Russia

Abstract: The study was based on the development of production functions that characterize the activities of agricultural enterprises in the regions of Russia. Official statistical information on 65 regions of Russia for 2017 and 2018 was used. The conducted research made it possible to identify factors (investments in fixed assets and wages of employees) that affect the volume of production in the agricultural sector in the regions of Russia and suggest using two-factor production functions of high quality to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…The importance of the rapid development of small businesses in all regions of Russia is explained for the period up to 2030. It is shown that, from 2015 to 2016, the number of small businesses and employees increased at the same time [10].…”
Section: Introductionmentioning
confidence: 97%
“…The importance of the rapid development of small businesses in all regions of Russia is explained for the period up to 2030. It is shown that, from 2015 to 2016, the number of small businesses and employees increased at the same time [10].…”
Section: Introductionmentioning
confidence: 97%